Structural, Electrochemical, and Photochemical Properties of Mono‐ and Digold(I) Complexes Containing Mesoionic Carbenes. Issue 14 (11th April 2017) - Hettmanczyk, Lara; Spall, Steven J. P.; Klenk, Sinja; van der Meer, Margarethe; Hohloch, Stephan; Weinstein, Julia A.; Sarkar, Biprajit
Abstract : Triazolylidenes are a prominent class of mesoionic carbenes (MICs) that are currently widely used in organometallic chemistry. Usually the metal complexes of such ligands are used as homogeneous catalysts even though they have vast potential in other branches of chemistry. We present here three related gold(I) complexes with MIC ligands: a neutral mononuclear chlorido complex [AuCl(MIC)], a cationic mononuclear complex containing two MIC ligands [Au(MIC)2 ]BF4, and a dicationic digold(I) complex containing two di‐MIC ligands [Au2 (κ 1, κ 1, µ‐di‐MIC)2 ](BF4 )2 . The complexes were characterized by 1 H and 13 C 1 H NMR spectroscopy, mass spectrometry, and single‐crystal X‐ray diffraction. The gold(I) centers are linearly coordinated through either one MIC‐ C and chlorido donors or through two MIC‐ C donors. The triazolylidenes display a delocalized bonding situation within the ring. Additionally, a short Au–Au distance of about 3 Å is observed for the digold(I) complex. All complexes display reduction steps in their cyclic voltammograms, and these are assigned to the reduction of the MIC ligands, as opposed to the generation of gold(0). The complexes emit at ca. 500 nm, with lifetimes of several microseconds in deoxygenated solutions; the emission intensity and lifetime are strongly decreased by the presence of oxygen, supporting the triplet origin of the emissive state. The present results display the utility of MIC ligands for generating electro‐ and photoactive molecules. Abstract : Mono‐ and dinuclear gold(I) complexes display a triazolylidene‐based reduction as well as excited‐state lifetimes of several microseconds.